2017
DOI: 10.1177/1744806917728227
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nociceptive interactions between opioids and a cannabinoid receptor 2 agonist in inflammatory pain

Abstract: The cannabinoid 1 receptor and cannabinoid 2 receptor can both be targeted in the treatment of pain; yet, they have some important differences. Cannabinoid 1 receptor is expressed at high levels in the central nervous system, whereas cannabinoid 2 receptor is found predominantly, although not exclusively, outside the central nervous system. The objective of this study was to investigate potential interactions between cannabinoid 2 receptor and the mu-opioid receptor in pathological pain. The low level of adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…The study also showed that sensation for a noxious stimulus, as classic preclinical model of analgesic activity, was additively diminished by the co-administration of THC with oxycodone compared with either drug administered alone. Prior work has shown antinociceptive interactions between muopioid and cannabinoid receptor ligands in formalin test of inflammatory pain (Yuill et al, 2017) and in nociception rhesus monkeys (Li et al, 2008). The present study extends those results to the interaction of THC with the effects of the prescription opioid oxycodone.…”
Section: Discussionsupporting
confidence: 77%
“…The study also showed that sensation for a noxious stimulus, as classic preclinical model of analgesic activity, was additively diminished by the co-administration of THC with oxycodone compared with either drug administered alone. Prior work has shown antinociceptive interactions between muopioid and cannabinoid receptor ligands in formalin test of inflammatory pain (Yuill et al, 2017) and in nociception rhesus monkeys (Li et al, 2008). The present study extends those results to the interaction of THC with the effects of the prescription opioid oxycodone.…”
Section: Discussionsupporting
confidence: 77%
“…AM1241 produced a modest enhancement of opioid-mediated antinociception in the hotplate test and in a test of mechanical sensitivity in tumor-bearing rats (Zhang et al, 2016); however, tolerance developed to the antiallodynic effects of the combination treatment assessed with mechanical but not thermal (hot plate) stimulation, suggesting that therapeutic benefit of the adjunctive treatment may be ligand-and/or modalitydependent. Coadministration of CB2 agonist JWH133 also exhibited opioid-sparing effects in the formalin model of inflammatory pain (Yuill et al, 2017). The mechanism underlying these therapeutically advantageous properties remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids are analgesic in several models of pain 5,[7][8][9][10][11] and act synergistically with opioids, 12 allow-ing for opioid sparing. Medicinal cannabis patients cite pain relief and opioid replacement as top reasons for use.…”
Section: Introductionmentioning
confidence: 99%
“…14 In contrast, preclinical studies report that cannabinoid-2 receptor (CB2R) agonism reduces acute, chronic, and inflammatory pain without psychoactive side effects. [8][9][10][11] However, the actions of cannabinoid compounds on respiration and interactions with opioid respiratory depression are unknown.…”
Section: Introductionmentioning
confidence: 99%